Development of MyHomePharmacy: A personalized family medicine management - Hashim, A.S. (Institute of Electrical and Electronics Engineers Inc., 2016)
There have been many studies which have been conducted on the development of healthcare system by incorporating smartphones such as pharmacy management system. However, the existing systems were limited to storing medicine inventory of pharmacy. Therefore, this paper introduces MyHomePharmacy which is a personalized family medicine management which runs on mobile web platform. Personalized here refers to the function provided where it allows the users to customize the system to manage medicine inventory for their family usage. Interview method has been applied for requirement gathering analysis. All requirements have been classified into functional and non-functional requirements and then depicted in the form of Unified Modelling Language (UML) diagrams for development purposes. Prototype has been developed using Adobe PhoneGap that allows the developed prototype to be accessed via Web platform. Functionality test was conducted where it was found that 60 rated good and 80 functionality success for both tests respectively. All recommendations and improvements about the prototype are recorded for future reference and alteration. Â© 2016 IEEE.